The chaos machine : the inside story of how social media rewired our minds and our world - Fisher, Max (Little, Brown and Company, 2022)
The gripping and galling inside story of how Facebook, Twitter, YouTube, and other social networks preyed on psychological frailties to create the algorithms that drive everyday users to extreme opinions and, increasingly, extreme actions. The companies' founding tenets, combined with a blinkered focus on maximizing engagement, have led to a destabilized world for everyone. -- adapted from jacket